Impact of Long-Term Organic and Mineral Fertilization on Rhizosphere Metabolites, Root–Microbial Interactions and Plant Health of Lettuce - Windisch, Saskia; Sommermann, Loreen; Babin, Doreen; Chowdhury, Soumitra Paul; Grosch, Rita; Moradtalab, Narges; Walker, Frank; Höglinger, Birgit; El-Hasan, Abbas; Armbruster, Wolfgang; Nesme, Joseph; Sørensen, Søren Johannes; et al. (Frontiers in Microbiology, 2021)
Fertilization management affects not only plant performance but also soil microbiota, with specific rhizosphere interactions influenced by root activity, still poorly understood. We assumed that long-term fertilization exerts selective effects on rhizodeposition with consequences for recruitment of rhizosphere microbiota and plant performance. To address this hypothesis, we conducted a minirhizotron-experiment with lettuce as model plant, using field soils with contrasting properties from two long-term field experiments (HUB-LTE: loamy sand, DOK-LTE: silty loam) with organic and mineral fertilization history. Although no consistent fertilization effects were detectable on alpha-diversity of fungal and prokaryotic/archaeal rhizosphere communities, increased abundance of plant-beneficial arbuscular-mycorrhizal fungi was characteristic for the rhizospheres of the organically managed soils (HU-org; BIODYN2). However, their rhizosphere microbiota also comprised more fungal pathotrophs, and the plants systemically expressed defense-related genes in shoot tissues. However, there was no consistent effect of fertilization history on shoot biomass and root development, which remained unaffected in HUB-LTE. In the BIODYN2 soil, shoot and root growth was severely suppressed and affected by Olpidium infection, coinciding with the highest rhizosphere abundance of the pathogen (89 %). This was associated with a reduction of potentially plant growth-promoting microorganisms, such as Pseudomonaceae and Mortierella elongata by 87 and 97 %. These profound alterations of rhizosphere microbial communities were linked with characteristic changes in the composition of the rhizosphere solution. Olpidium-induced growth suppression and low rhizosphere abundance of Pseudomonadaceae were associated with reduced rhizosphere concentrations of the antifungal root exudate benzoic acid. This metabolite was described in the literature to be increased by Pseudomonas inoculation. By contrast, high abundance of Pseudomonadaceae (Gammaproteobacteria) in the rhizosphere of plants with long-term mineral fertilization (61-74 %) coincided with high rhizosphere concentrations of chemotactic dicarboxylates (succinate, malate) and a high C (sugar)/N (amino acid) ratio, known to support the growth of Gammaproteobacteria. Under these conditions no plant growth depressions were recorded even in presence of a high Olpidium abundance (76 %) in the rhizosphere. Our results suggest a complex network of belowground interactions between crop roots, site-specific factors and rhizosphere microbiota, modulating the impact of fertilization management with consequences for plant health and crop performance.